Geographical Characterization of West Java Clove by FTIR and Chemometrics PCA Analysis - Rachmawati, Winasih; Khoirunnisa, Intan; Asnawi, Aiyi (Indonesian Journal of Pharmaceutical Science and Technology, 2026)
Clove is a plant native to West Java, Indonesia, and its composition has been scientifically proven to have antioxidant, antibacterial, antinociceptive, and cytotoxic effects. The quality of a plant is influenced by its growth location, harvest time, and genetic attributes. This study was designed to determine the characteristics of the cloves from West Java. This study aimed to develop a clove fingerprint profile using Fourier transform infrared (FTIR) spectroscopy and principal component analysis (PCA) chemometrics across five regions of West Java. Clove flowers were collected from Bandung, Bogor, Purwakarta, Cianjur, and Tasikmalaya, Indonesia. The cloves were then extracted by maceration with 96% ethanol for three 24-hour periods. The extract was analyzed by FTIR over 4000-650 cm-1 and then subjected to preprocessing steps, including smoothing, differentiation, and Standard Normal Variate. A cumulative PC value of 91% formed three clusters with similar qualities in the score plot: Group 1 (Purwakarta), Group 2 (Bandung, Cianjur, and Tasikmalaya), and Group 3 (Bogor). Chemometric analysis can be used to authenticate and classify cloves based on geographical distribution.